Efficacy of natural products on premature ovarian failure: a systematic review and meta-analysis of preclinical studies - Hangqi Hu; Jiacheng Zhang; Xiyan Xin; Yuxin Jin; Yutian Zhu; Haolin Zhang; Ruiwen Fan; Yang Ye; Dong Li (BMC, 2024)
Abstract Objective This study aims to investigate the effects of natural products on animal models of premature ovarian failure (POF). Methods We conducted comprehensive literature searches and identified relevant studies that examined the protective effects of natural products on experimental POF. We extracted quantitative data on various aspects such as follicular development, ovarian function, physical indicators, oxidative stress markers, inflammatory factors, and protein changes. The data was analyzed using random-effects meta-analyses, calculating pooled standardized mean differences and 95% confidence intervals. Heterogeneity was assessed using the I2 statistic, and bias was estimated using the SYRCLE tool. Results Among the 879 reviewed records, 25 articles met our inclusion criteria. These findings demonstrate that treatment with different phytochemicals and marine natural products (flavonoids, phenols, peptides, and alkaloids, etc.) significantly improved various aspects of ovarian function compared to control groups. The treatment led to an increase in follicle count at different stages, elevated levels of key hormones, and a decrease in atretic follicles and hormone levels associated with POF. This therapy also reduced oxidative stress (specifically polyphenols, resveratrol) and apoptotic cell death (particularly flavonoids, chrysin) in ovarian granulosa cells, although it showed no significant impact on inflammatory responses. The certainty of evidence supporting these findings ranged from low to moderate. Conclusions Phytochemicals and marine natural product therapy (explicitly flavonoids, phenols, peptides, and alkaloids) has shown potential in enhancing folliculogenesis and improving ovarian function in animal models of POF. These findings provide promising strategies to protect ovarian reserve and reproductive health. Targeting oxidative stress and apoptosis pathways may be the underlying mechanism.